Benefits of cooperation in captive Damaraland mole-rats. (12th March 2020) - Houslay, Thomas M; Vullioud, Philippe; Zöttl, Markus; Clutton-Brock, Tim H
Abstract: Although the social mole-rats are commonly classified as eusocial breeders on the grounds that groups include a single breeding female (the "queen") and a number of nonbreeding individuals ("helpers") of both sexes, alloparental care is not highly developed in these species and there is no direct evidence that the presence or number of nonbreeders is associated with reductions in the workload of the "queen." An alternative interpretation of mole-rat groups is that the social mole-rats are cooperative foragers rather than cooperative or eusocial breeders. Here, in captive colonies of Damaraland mole-rats ( Fukomys damarensis ), we provide the first evidence that increases in the number of nonbreeding subordinates in mole-rat groups are associated with reductions in the workload of "queens" and with increases in their fecundity. Abstract : Social mole-rats are commonly classified as cooperative or eusocial breeders, yet nonbreeding helpers do not provision juveniles or queens directly and there is no evidence that helpers reduce the workload or increase the breeding success of queens. Here, we show that, as group size (and cumulative helper workload) increases, queens work less, feed and rest more, and have higher breeding success. Our results confirm that social mole-rats are described correctly as cooperative breeders.